Studies on Stigma Receptivity in Indian Mustard - K.S. MANKAR; J.B. YADAV; N.C. SINGHAL; SURENDRA PRAKASH; ASHOK GAUR (Seed Research, 2026)
Stigma receptivity in different CMS lines and genotypes of mustard was studied by pollinating the stigmas daily upto 8 days of starvation. Seed bearing siliquae developed on pollinated buds and seed per siliquae were counted at maturity. Stigma receptivity was found to be at its peak a day before anthesis which declined gradually upto 3-5 days and drastically thereafter. Stigma ceased to be receptive after 6-8 days. Plants kept on pollination starvation, increased spike length, flowering duration and stigma per flower for capturing the pollen.